Pengaruh Pengetahuan Terhadap Sosialisasi Ziswaf Kepada Masyarakat Dan Anak-Anak Di Kampung Rukti Basuki Satu - Lulu Latifatul Agy Nabela; Kiki Khoirunnisa; Toto Andri Puspito; Saipullah (Universitas Darunnajah, Jakarta, Indonesia, 2024)
This community service activity aims to increase the knowledge of the people of Kampung Rukti Basuki Satu about Islamic economics through socialization activities. Because the interest of the people of Kampung Rukti Basuki Satu to study Islamic economics is still low. This activity is carried out with an active participation method through socialization to the community about the benefits of knowing the Islamic economic system in everyday life. Socialization as the author's media in preventing the community from continuing to use and recognize the conventional economic system. The result of the socialization of Islamic economics is the increased knowledge of the people of Rukti Basuki Satu Village about LKMS and ZISWAF. Based on these results, it is hoped that the community will continue to explore other knowledge in the field of Islamic economics.